Satellite Orbits [electronic resource] : Models, Methods and Applications / by Oliver Montenbruck, Eberhard Gill. - Montenbruck, Oliver (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2000., 2018)
XI, 369 p. digital.